2015
DOI: 10.1186/s12933-015-0176-5
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between advanced glycation end products (AGEs)-receptor RAGE axis and dipeptidyl peptidase-4-incretin system in diabetic vascular complications

Abstract: Advanced glycation end products (AGEs) consist of heterogenous group of macroprotein derivatives, which are formed by non-enzymatic reaction between reducing sugars and amino groups of proteins, lipids and nucleic acids, and whose process has progressed at an accelerated rate under diabetes. Non-enzymatic glycation and cross-linking of protein alter its structural integrity and function, contributing to the aging of macromolecules. Furthermore, engagement of receptor for AGEs (RAGE) with AGEs elicits oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 157 publications
(220 reference statements)
1
79
0
1
Order By: Relevance
“…Cutaneous AGEs accumulation may hinder the photoconversion of provitamin D into vitamin D, mechanism that, in physiological conditions, accounts for 80 % of overall vitamin D balance. Interestingly, linagliptin was shown to prevent the AGE-receptor gene expression [30] and to improve diabetic wound healing in diabetic mice by directly inhibiting DPP4 activity in keratinocytes [31]. Therefore, DPP4-Is may locally improve vitamin D synthesis by modulating AGEs deposition and DPP4 activity in the skin, with favorable effects on bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous AGEs accumulation may hinder the photoconversion of provitamin D into vitamin D, mechanism that, in physiological conditions, accounts for 80 % of overall vitamin D balance. Interestingly, linagliptin was shown to prevent the AGE-receptor gene expression [30] and to improve diabetic wound healing in diabetic mice by directly inhibiting DPP4 activity in keratinocytes [31]. Therefore, DPP4-Is may locally improve vitamin D synthesis by modulating AGEs deposition and DPP4 activity in the skin, with favorable effects on bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Several candidate mechanisms that RAGE contributes to chronic diseases have been proposed. Conjugation of RAGE with AGEs induces oxidative stress and subsequently causes the occurrence of proliferative, inflammatory, and fibrotic reactions in a variety of cells (Motoyoshi et al 2014;Yamagishi et al 2015). The pathogenesis is hypothesized to include ligand binding to activate RAGE signals and trigger inflammatory response (Heilmann et al 2014;Zhang et al 2014).…”
Section: Ages and Ragementioning
confidence: 99%
“…There is a pathological crosstalk between the AGE-RAGE system and dipeptidyl peptidase-4 (DPP-4)-incretin axis in the pathogenesis of vascular complications in diabetes (95,96). Glucagonlike peptide-1 directly acts on endothelial cells, mesangila cells and proximal tubular cells via the glucagon-like peptide-1 receptor, and glucagon-like peptide-1 could work as an antiinflammatory and antioxidative agent against AGEs by reducing RAGE expression via activation of cyclic AMP pathways (95,96).…”
Section: Dipeptidyl Peptidase-4 Inhibitors and Incretinsmentioning
confidence: 99%
“…Glucagonlike peptide-1 directly acts on endothelial cells, mesangila cells and proximal tubular cells via the glucagon-like peptide-1 receptor, and glucagon-like peptide-1 could work as an antiinflammatory and antioxidative agent against AGEs by reducing RAGE expression via activation of cyclic AMP pathways (95,96). Moreover, we have recently found that AGE-RAGE-induced oxidative stress generation stimulates the release of DPP-4 from endothelial cells, which could act on endothelial cells in an autocrine manner via the interaction with mannose 6-phosphate insulin-like growth factor II receptor, further potentiating the deleterious effects of AGEs (97).…”
Section: Dipeptidyl Peptidase-4 Inhibitors and Incretinsmentioning
confidence: 99%